Investments in education: The early years offer great potential - C. Katharina Spieß (DIW Economic Bulletin, 2013)
Investments in education are of great importance for the competitiveness of the German economy. In particular, early childhood education programs promise high returns - because children can benefit from them even years later and find it easier to acquire new skills. These are the results of research in the field of the economics of education in recent years, at least when high quality programs are studied. However, these findings do not necessarily reflect public spending on the different education sectors - in reality, comparatively little is invested in young children. There is a need for more investment in education - especially to increase the quality of education programs - but not only in early childhood. Also, with regard to the expansion of all-day schools, more should be invested in the quality of such programs. In higher education, efforts are needed to improve access of educationally disadvantaged groups and therefore improve intergenerational mobility. All these measures could facilitate a more effective and efficient use of human capital. This is also of particular importance against the backdrop of a forecast decline in labor force potential and predicted skill shortages.
Keywords: I2; I22; I28; 330; education policy; early education; rate of return; investments